Beyond Enforcement: The Effect of Adult Tax Education on Tax Morale in Indonesia - Ariefianto, Lutfi; Sartika, Rody Putra; Puspitaningsih, Arin Ika (Institut Teknologi Pendidikan Indonesia, 2026)
This study investigates the effect of adult tax education on tax morale in Indonesia, moving beyond the traditional enforcement-centric approach to tax compliance. Utilizing a mixed-methods research design, we combined a quantitative survey of 400 adult taxpayers in East Java with a qualitative thematic analysis of in-depth interviews. The quantitative results, analyzed through multiple linear regression, revealed a significant and positive effect of adult tax education on tax morale (β=0.87,p<0.001). This finding indicates that participation in non-formal tax education programs is a strong predictor of an individual's intrinsic motivation to pay taxes. The qualitative findings provide rich context, highlighting a shift in taxpayers' perceptions from viewing taxes as a financial burden to a civic responsibility. Participants' narratives consistently emphasized that education demystified the tax system, rebuilt trust in government, and fostered a sense of shared community responsibility. These findings have critical implications for fiscal policy, suggesting that investing in targeted educational initiatives is a more sustainable and effective strategy for fostering voluntary tax compliance than relying solely on punitive measures. This study fills a significant gap in the literature by providing robust, causal evidence in the Indonesian context, offering a new path for building a more cooperative relationship between taxpayers and the state.